Economics of cultivation of important trees in farmlands in Tamil Nadu - Buvaneswaran, C.; Saravanan, S.; Jayaraj, R.S.C. (Indian Journal of Agroforestry, 2020)
The farmers' choice of tree species depends mainly on high economic returns, short rotation, assured marketability and demands from wood based industries. The above factors have favoured cultivation of tree species such as Casuarina, Eucalypts, Teak and Aonla in Tamil Nadu. The experiences of farmers in cultivation of these preferred species under plantation and agroforestry systems is discussed in this paper along with economics of cultivation and limitations thereof.